THE strategic of implementation health and safety to improved performance construction management system (Case in Arcamanic project, Indonesia) - H Sutawijaya, Achmad; C Nawangsari, Lenny (International Journal of Engineering and Technology, 2018)
Implementation of management systems on health, safety and environment (HSE) in Indonesia is still not optimally implemented, this is because the safety culture is not rooted among the people. Accidents occurred in construction activities will have direct impact on safety construction time, productivity losses and every individual involved in the work. These concerns are responsibility of company that must be addressed by the delivery of an integrated management strategy of quality, health and safety and environment. This study aims to obtain strategic implementation model in occupational safety and health to improve performance, particularly on construction activity. Qualitative and philosophical approaches are methods that used in this research. This research is located at construction area of SPOrT Jabar Arcamanik Indonesia with 10 (ten) research subjects involved. This research indicated that in order to improve performance in construction management, the system must be integrated with safety management strategy which are categorized in three sub area: structure policy organization, procedures and implementation. The implementation of this integration is expected to establish a culture of safety in the context of behavior and environment. In conclusion, the implementation of this project will improve performance in construction activities.Â